Bacteria Material in the Short Story Based on the Characters of Punokawan for Biology Learning - Endah Rita Sulistya Dewi; . Prasetiyo (Bandar Lampung University (UBL), 2014)
Character building education can be internalized through education components as learning tools the form of teaching material. Bacteria material are abstract thing which may appears more attractive as a teaching material if it delivered through short stories which based from the Punokawan characters and figures. This kind of teaching strategies are expected to be something that can explore the local culture or local wisdom. The purpose of this study is to deliver the teaching material of Bacteria in Biology class in the form of short stories which based on Punokawan character, as well as the understanding concept of the students. It showed by providing teaching material in the form of short stories which contain of materials and character values will affected the excavation of character values and students’ understanding concept.